Impact of asymmetric uncertainties in ice sheet dynamics on regional sea level projections - R. C. de Winter; T. J. Reerink; A. B. A. Slangen; H. de Vries; T. Edwards; R. S. W. van de Wal (Natural Hazards and Earth System Sciences, 2017)
Currently a paradigm shift is made from global averaged to spatially variable sea level change (SLC) projections. Traditionally, the contribution from ice sheet mass loss to SLC is considered to be symmetrically distributed. However, several assessments suggest that the probability distribution of dynamical ice sheet mass loss is asymmetrically distributed towards higher SLC values. Here we show how asymmetric probability distributions of dynamical ice sheet mass loss impact the high-end uncertainties of regional SLC projections across the globe. For this purpose we use distributions of dynamical ice sheet mass loss presented by Church et al. (2013), De Vries and Van de Wal (2015) and Ritz et al. (2015). The global average median can be 0.18 m higher compared to symmetric distributions based on IPCC-AR5, but the change in the global average 95th percentile SLC is considerably larger with a shift of 0.32 m. Locally the 90th, 95th and 97.5th SLC percentiles exceed +1.4, +1.6 and +1.8 m. The high-end percentiles of SLC projections are highly sensitive to the precise shape of the probability distributions of dynamical ice sheet mass loss. The shift towards higher values is of importance for coastal safety strategies as they are based on the high-end percentiles of projections.